2014
DOI: 10.1007/s10995-014-1542-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tube Defects in Costa Rica, 1987–2012: Origins and Development of Birth Defect Surveillance and Folic Acid Fortification

Abstract: Our aim was to provide a descriptive overview of how the birth defects surveillance and folic acid fortification programs were implemented in Costa Rica—through the establishment of the Registry Center for Congenital Anomalies (Centro de Registro de Enfermedades Congénitas—CREC), and fortification legislation mandates. We estimated the overall prevalence of neural tube defects (i.e., spina bifida, anencephaly and encephalocele) before and after fortification captured by CREC. Prevalence was calculated by divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
1
18
1
1
Order By: Relevance
“…The reduced prevalence observed in our study is lower than that observed in Chile 5 and Costa Rica, 14 but higher than that seen in Brazil. 5 Such variation may be due to the effectiveness of different fortification strategies: variations in dose, in selected basic foods, and in the FAF period that was assessed.…”
Section: Discussioncontrasting
confidence: 87%
“…The reduced prevalence observed in our study is lower than that observed in Chile 5 and Costa Rica, 14 but higher than that seen in Brazil. 5 Such variation may be due to the effectiveness of different fortification strategies: variations in dose, in selected basic foods, and in the FAF period that was assessed.…”
Section: Discussioncontrasting
confidence: 87%
“…La disminución de la prevalencia observada en nuestro trabajo es menor a la observada en Chile 5 y Costa Rica, 14 pero mayor a la observada en Brasil. 5 Esta variación puede deberse a la efectividad de diferentes estrategias de fortificación: variación en las dosis, en los alimentos básicos seleccionados y en el tiempo de FAF evaluado.…”
Section: Discussionunclassified
“…Protective levels of serum and RBC-folate are estimated to be > 18 nmol/L and > 1000 nmol/L respectively [9,20,21]. After introducing a population-wide fortification of staple foods with FA, the prevalence of NTDs in the US, Costa Rica [22], and many other countries declined to < 5-6 cases per 10,000 births and thus, it is now only about half as high as the average rate of 9.3 cases per 10,000 births in Europe in 2012 (source EUROCAT, University of Ulster). The pathogenesis of NTDs and the protective mechanisms of FA are still not well understood [23], but it appears that FA cannot prevent all NTD cases.…”
Section: Timely Supplementation Of Folate Prevents Birth Defectsmentioning
confidence: 99%
“…The fortification has shown to be effective in terms of lowering tHcy, increasing serum, and RBC-folate [80,81], eliminating anemia [82], and reducing NTD [22]. Fortification of staple foods requires supportive legislations or regulations, and its implementation and effects should be monitored.…”
Section: Improving Population Folate Statusmentioning
confidence: 99%